OPTIMIZATION OF HEALTHCARE WORKERS AVAILABILITY: INCREASING PRIMARY HEALTHCARE EFFICIENCY IN INDONESIA - Niedar, Anedya; Hafidz, Firdaus; Hort, Krishna (UI Scholars Hub, 2022)
Policy has focused on the unequal distribution of health workers, while the potential for improvements in efficiency to address this problem has been neglected. This study aims to measure and compare the level of efficiency in the use of the available health workforce for the delivery of selected primary healthcare services among districts/cities in Indonesia, and to identify factors influencing that efficiency. The Data Envelopment Analysis method with output orientation to measure efficiency and Tobit regression analysis was performed to determine the effect of contextual factors. The average score for the technical efficiency of primary health care service delivery throughout Indonesia was 1.29, indicating the potential to achieve on average 29% higher coverage of the selected primary health services if all were as efficient as the most efficient. The average efficiency score in the Eastern Indonesia region was 1.62 and the average in the Java-Bali region was 1.05, indicating higher potential efficiency gains in the Eastern Indonesia region. Access to health care facilities was a consistently significant factor influencing the efficiency of primary health care in almost all regions. This study has demonstrated the potential for significant gains in coverage of key primary care services through improvements in the efficiency of use of the existing health workforce.